2021
DOI: 10.1007/s10637-021-01068-8
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in anti-BRAF therapies for lung cancer

Abstract: SummaryNon-small cell lung cancer (NSCLC) is one of the most frequent causes of mortality in the western world. v-raf murine sarcoma viral oncogene homolog B (BRAF) is a member of the Raf kinase family and plays a critical role in cellular growth, proliferation, and differentiation through the mitogen-activated protein kinase pathway. The incidence of BRAF mutations in NSCLC is low, accounting for 0–3% of all cases of lung cancer. Given the results obtained in metastatic melanoma, several studies have reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 82 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…According to the guidelines for the treatment of NSCLC, identification of activating mutations of EGFR and ALK is recommended [ 2 ]. According to the literature, 10–13% of Caucasian patients with adenocarcinoma (which represents the most part of non-squamous NSCLC) presents an EGFR activating mutation, 2–7% rearrangements of ALK and 1–4% BRAF mutations [ 2 , 22 ]. In line with these data, about 10% of patients with non-squamous NSCLC in our study cohort were treated with target therapies.…”
Section: Discussionmentioning
confidence: 99%
“…According to the guidelines for the treatment of NSCLC, identification of activating mutations of EGFR and ALK is recommended [ 2 ]. According to the literature, 10–13% of Caucasian patients with adenocarcinoma (which represents the most part of non-squamous NSCLC) presents an EGFR activating mutation, 2–7% rearrangements of ALK and 1–4% BRAF mutations [ 2 , 22 ]. In line with these data, about 10% of patients with non-squamous NSCLC in our study cohort were treated with target therapies.…”
Section: Discussionmentioning
confidence: 99%
“…When we constructed PPI networks of molecules elevated by cDNA microarray and proteomic analysis, both networks were similar ( Supplementary Figures S1 and S2 ). Although there are many reports on the induction of cancer cell differentiation and growth inhibition [ 47 , 48 ], there are almost no reports on the involvement of HBp17. It was reported that FLG expression increases in HBp17 -KO mice [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the favorable responses shown in patients with other aggressive neoplasms such as melanoma, the use of different targeted therapies has been studied, with the V600E mutation being the most frequent in lung adenocarcinoma. Patients with BRAF mutations tend to have a better prognosis than those without mutations, as this conditions a better response to immunotherapeutic treatment with dabrafenib and trametinib ( 53 ). Another type of molecular alteration described are alterations in tropomyosin receptor kinases, which are present in <1% of adenocarcinomas that are candidates for treatment with larotrectinib and entrectatinib, reaching response rates of up to 80% and a median survival of 90 months ( 54 ).…”
Section: Molecular and Histological Markers In Lung Cancermentioning
confidence: 99%